FORMATION OF AN INNOVATIVE MODEL FOR THE DEVELOPMENT OF INDUSTRIAL ENTERPRISES - TERENTIEVA Оlena; DATSENKO, Nataliia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Modern industry is undergoing a profound and systemic paradigm shift driven by the convergence of advanced Industry 4.0 technologies, the global transition toward servitization, and heightened geopolitical instability. These processes have significantly increased the importance of innovative development integrated with digital technologies as a decisive factor for maintaining the competitiveness and resilience of industrial enterprises. The article examines the conceptual foundations and practical challenges of digital transformation, emphasizing the need for a holistic and adaptive approach to innovation management. The main barriers identified include technological fragmentation, insufficient digital maturity, organizational resistance to change, and limited interoperability between systems. To address these challenges, the paper proposes a synergistic innovation model as a structured, dynamic framework for industrial development. The model is based on four interconnected pillars: an open digital ecosystem that supports collaboration and co-creation; intelligent infrastructure integrating Industry 4.0 tools such as IoT, AI, and cloud computing; organizational flexibility that enables rapid adaptation; and a data-driven culture fostering evidence-based decision-making. For practical implementation, a four-phase roadmap is developed, including strategic diagnostics, detailed design, pilot implementation, and large-scale organizational transformation. The model operates on the principles of flexibility, customer orientation, and continuous learning, ensuring alignment between internal capabilities and external innovation dynamics. The article also provides practical recommendations for minimizing risks during the transition, including strategic licensing of proven digital solutions, the use of agile methodologies, and the Lean Startup approach (MVP testing). The synergistic innovation model is shown to be an essential conceptual and practical framework for digital transformation, allowing enterprises to evolve into continuously learning, adaptable systems that effectively integrate technological progress with strategic management.